Distribution of leaf characteristics in relation to orientation within the canopy of woody species - Escudero, Alfonso; Fernández, José; Cordero, Angel; Mediavilla, Sonia (Acta Oecologica, 2013)
Over the last few decades considerable effort has been devoted to research of leaf adaptations to environmental conditions. Many studies have reported strong differences in leaf mass per unit area (LMA) within a single tree depending on the photosynthetic photon flux density (PPFD) incident on different locations in the crown. There are fewer studies, however, of the effects of differences in the timing of light incidence during the day on different crown orientations. Leaves from isolated trees of Quercus suber and Quercus ilex in a cold Mediterranean climate were sampled to analyze differences in LMA and other leaf traits among different crown orientations. Gas-exchange rates, leaf water potentials, leaf temperatures and PPFD incident on leaf surfaces in different crown orientations were also measured throughout one entire summer day for each species. Mean daily PPFD values were similar for the leaves from the eastern and western sides of the canopy. On the western side, PPFD reached maximum values during the afternoon. Maximum leaf temperatures were approximately 10–20% higher on the west side, whereas minimum leaf water potentials were between 10 and 24% higher on the east side. Maximum transpiration rates were approximately 22% greater on the west, because of the greater leaf-to-air vapor pressure deficits (LAVPD). Mean individual leaf area was around 10% larger on the east than on the west side of the trees. In contrast, there were no significant differences in LMA between east and west sides of the crown. Contrary to our expectations, more severe water stress on the west side did not result in increases in LMA, although it was associated with lower individual leaf area. We conclude that increases in LMA measured by other authors along gradients of water stress would be due to differences in light intensity between dry and humid sites.
Keywords: Canopy orientation; leaf morphology; Leaf temperature; Quercus; water potential

Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Water-use strategies of six co-existing Mediterranean woody species during a summer drought - Quero, JoséL.; Sterck, FrankJ.; Martínez-Vilalta, Jordi; Villar, Rafael (Oecologia, 2011)
Drought stress is known to limit plant performance in Mediterranean-type ecosystems. We have investigated the dynamics of the hydraulics, gas exchange and morphology of six co-existing Mediterranean woody species growing under natural ﬁeld conditions during a drought that continued during the entire summer. Based on the observed minimum leaf water potentials, our results suggest that the six co-existing species cover a range of plant hydraulic strategies, from isohydric to anisohydric. These differences are remarkable since the selected individuals grow within several meters of each other, sharing the same environment. Surprisingly, whatever the leaf water potentials were at the end of the dry period, stomatal conductance, photosynthesis and transpiration rates were relatively similar and low across species. This result contradicts the classic view that anisohydric species are able to maintain gas exchange for longer periods of time during drought stress. None of the plants showed the expected structural acclimation response to the increasing drought (reduction of leaf-to-sapwood area ratio), thereby rejecting the functional equilibrium hypothesis for our study system. Instead, three of the six species increased photosynthetic area at the branch level. The observed dissimilar patterns of gas exchange, hydraulics and morphology across species seem to be equally successful given that photosynthesis at the leaf level was maintained at similar rates over the whole dry period.
Keywords: Anisohydric; embolism; Isohydric; photosynthesis; Stomatal conductance; water potential

Facilitation of Quercus ilex in Mediterranean shrubland is explained by both direct and indirect interactions mediated by herbs - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Rey Benayas, José M.; Michalet, Richard (Journal of Ecology, 2010)
1. Competitive and facilitative interactions shape plant communities. Whereas a number of studies have addressed competition and direct facilitation among plants in dry ecosystems, indirect facilitation has received little attention. 2. We investigated the relative importance of direct and indirect facilitation by the nurse plant Retama sphaerocarpa on late-successional Quercus ilex seedlings mediated by herb suppression in a Mediterranean shrubland in 2006 and 2007. We also studied whether facilitation outcome depended on the size of the facilitated seedlings. 3. A field experiment was carried out to test the effect of (i) position of Q. ilex seedling with respect to shrub canopy (under shrubs or in gaps), (ii) herb competition (presence or absence), and (iii) seedling size. 2006 was an average rainfall year while 2007 had a much more humid spring and a dryer summer than 2006. 4. In both years, nurse shrubs reduced seedling mortality whereas herbs increased it. In the average rainfall year, seedling mortality under shrubs was unaffected by herbs whereas in gaps it was significantly higher in presence of herbs. This showed that the nurse shrub indirectly facilitated the seedlings by reducing the competitive capacity of herbs. Conversely, facilitation was predominately direct during the humid spring and dry summer year since herbs hindered seedling survival similarly under the nurse shrub and in gaps. The nurse shrub directly facilitated the seedlings by reducing seedling photoinhibition and water stress. 5. Improvement of environmental conditions by Retama benefited smaller seedlings but not larger seedlings since the nurse shrub reduced mortality of smaller seedlings relative to that in gaps, but this effect was not observed for larger seedlings. This indicates that individuals within a seedling population may not have the same response to facilitation. 6. Synthesis. Both indirect and direct facilitation are important mechanisms for Q. ilex regeneration in Retama shrubland and their importance seems to vary with climatic conditions. Indirect facilitation by release of herb competition under nurse shrubs is important in years of dry springs when competition between nurse shrubs and herbs is high, whereas direct facilitation mediated by microclimate amelioration increases with summer aridity.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: chlorophyll fluorescence; herb competition; Quercus ilex; retama sphaerocarpa; seedling size; water potential

Why do large, nitrogen rich seedlings better resist stressful transplanting conditions? A physiological analysis in two functionally contrasting Mediterranean forest species - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Jacobs, Douglass F.; Rey Benayas, José M. (Forest Ecology and Management, 2010)
We analysed the physiological bases that explain why large and high nitrogen (N) concentration seedlings frequently have improved survival and growth relative to small seedlings in Mediterranean woodland plantations. Large seedlings of Aleppo pine (Pinus halepensisMill.) and holm oak (Quercus ilex L.) with high N concentration (L+), and small seedlings with either high (S+) or low (S−) N concentration, were planted on two sites of different weed competition intensity that created contrasting stress conditions. Seedling survival, growth, gas exchange, N remobilization (NR) and uptake (NU), and water potential were assessed through the ﬁrst growing season. Weeds reduced survival and growth, but seedling response to weed competition varied among phenotypes and between species. At the end of the ﬁrst growing season, L+ Aleppo pine seedlings had higher survival than both small seedling types in presence of weeds but no differences were observed in absence of weeds. Mortality differences among phenotypes occurred in spring but not in summer. L+ Aleppo pines grew more than small Aleppo pines independently of weed competition. No holm oak seedling type survived in presence of weeds and no mortality differences among phenotypes where observed in absence of weeds, although L+ holm oak seedlings grew more than small seedlings. Mortality and growth differences in Aleppo pine were linked to marked physiological differences among phenotypes while physiological differences were small among holm oak phenotypes. L+ Aleppo pines had greater root growth, gas exchange, NR, and NU than small seedlings, irrespective of their N concentration. Seedling size in Aleppo pine had a greater role in the performance of transplanted seedlings than N concentration. The functional differences among oak phenotypes were small whereas they were large in pine seedlings, which led to smaller differences in transplanting performance in holm oak than in pine. This suggests that the nursery seedling quality improvement for planting in dry sites could depend on the species-speciﬁc phenotypic plasticity and functional strategy. Improved transplanting performance in large Aleppo pine seedlings relative to small seedlings was linked to greater gas exchange, root growth and N cycling.
Keywords: competition; Nitrogen remobilization; photosynthesis; Pinus halepensis; Quercus ilex; Root growth; Stomatal conductance; Survival; water potential

Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland - Carevic, F S; Fernández, M; Alejano, R; Vázquez-Piqué, J; TAPIAS, R; Corral, E; Domingo, J (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an
Keywords: acorn production; cuticular transpiration; land use; pressure-volume curves; soil treatments; water potential

Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland - Carevic, F. S.; Fernández, M.; Alejano, R.; Vázquez-Piqué, J.; Tapias, R.; Corral, E.; Domingo, J. (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an
Keywords: acorn production; cuticular transpiration; land use; pressure-volume curves; soil treatments; water potential

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Contribution of physiological and morphological adjustments to drought resistance in two Mediterranean tree species - Serrano, L; Penuelas, J (Biologia Plantarum, 2005)
Plant water potential (ψ), its components, and gas exchange data of two Mediterranean co-occurring woody species (Quercus ilex L. and Phillyrea latifolia L.) were measured in response to seasonal changes in water availability over two consecutive years. The relative contribution of physiological and morphological adjustments to drought resistance was assessed through Principal Component Analyses. There were large adjustments in stomatal conductance (~36 % of accounted variance). Net photosynthetic rate and water use efficiency were closely tuned to water availability and accounted for ~17 % of variance. The slope of the water potential vs. relative water content (dψ/dRWC0) below zero pressure potential increased as a result of seasonal and ontogenic increases in apoplastic water fraction and accounted for ~20 % variance. This tolerance mechanism was accompanied by an increased range of positive pressure potential, suggesting a functional role of sclerophylly in these Mediterranean evergreens. Similarly, changes in the slope of dψ/dRWC in the range of positive pressure potential (~13 % of accounted variance) were associated to variations in cell wall elasticity and resulted in lower RWC at zero pressure potential. When considering the species studied separately, the results indicated the primary role of stomatal regulation in the drought resistance of Q. ilex, while increased apoplastic water fraction had a major contribution in the drought resistance of P. latifolia.
Keywords: Drought stress; net photosynthetic rate; phillyrea latifolia; plant and tissue-water relations; Quercus ilex; Stomatal conductance; water potential

Contribution of physiological and morphological adjustments to drought resistance in two Mediterranean tree species - Serrano, L.; Penuelas, J. (Biologia Plantarum, 2005)
Plant water potential (ψ), its components, and gas exchange data of two Mediterranean co-occurring woody species (Quercus ilex L. and Phillyrea latifolia L.) were measured in response to seasonal changes in water availability over two consecutive years. The relative contribution of physiological and morphological adjustments to drought resistance was assessed through Principal Component Analyses. There were large adjustments in stomatal conductance (~36 % of accounted variance). Net photosynthetic rate and water use efficiency were closely tuned to water availability and accounted for ~17 % of variance. The slope of the water potential vs. relative water content (dψ/dRWC0) below zero pressure potential increased as a result of seasonal and ontogenic increases in apoplastic water fraction and accounted for ~20 % variance. This tolerance mechanism was accompanied by an increased range of positive pressure potential, suggesting a functional role of sclerophylly in these Mediterranean evergreens. Similarly, changes in the slope of dψ/dRWC in the range of positive pressure potential (~13 % of accounted variance) were associated to variations in cell wall elasticity and resulted in lower RWC at zero pressure potential. When considering the species studied separately, the results indicated the primary role of stomatal regulation in the drought resistance of Q. ilex, while increased apoplastic water fraction had a major contribution in the drought resistance of P. latifolia.
Keywords: Drought stress; net photosynthetic rate; phillyrea latifolia; plant and tissue-water relations; Quercus ilex; Stomatal conductance; water potential

SEASONAL PATTERN OF PHYSIOLOGICAL STATE IN A CORK OAK (QUERCUS SUBER L.) STAND IN HUELVA (SPAIN) - GONZÁLEZ-PÉREZ, ARANTZAZU; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL; FERNÁNDEZ, MANUEL (Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005., 2005)
The seasonal pattern of the physiological state of Quercus suber is determined by different ecological factors, and it affects to the growth of the species. The main objective of this study is to know the seasonal pattern of water potential, photosynthesis and fluorescence in four Quercus suber L. trees and to relate these values with ecological factors during two years. In this time there were three critical periods, the first one the end of the dry period where the water potential descends to values less than -3MPa and the photosynthesis to 0.781 µmol CO2m-2 s-1Quercus suber, physiology, water potential, photosynthesis, fluorescence. . The second critical period is located in period of change of the leaf, between the months of March and May. The third critical period occurred due to the freezes and drought of the year 2005, that produced strong damages in the PSII.
Keywords: fluorescenc; photosynthesis; physiology; Quercus suber; water potential

SEASONAL PATTERN OF PHYSIOLOGICAL STATE IN A CORK OAK (QUERCUS SUBER L.) STAND IN HUELVA (SPAIN) - GONZÁLEZ-PÉREZ, ARANTZAZU; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL; FERNÁNDEZ, MANUEL (Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005., 2005)
The seasonal pattern of the physiological state of Quercus suber is determined by different ecological factors, and it affects to the growth of the species. The main objective of this study is to know the seasonal pattern of water potential, photosynthesis and fluorescence in four Quercus suber L. trees and to relate these values with ecological factors during two years. In this time there were three critical periods, the first one the end of the dry period where the water potential descends to values less than -3MPa and the photosynthesis to 0.781 µmol CO2m-2 s-1Quercus suber, physiology, water potential, photosynthesis, fluorescence. . The second critical period is located in period of change of the leaf, between the months of March and May. The third critical period occurred due to the freezes and drought of the year 2005, that produced strong damages in the PSII.
The following values have no corresponding Zotero field: periodical: Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005. pub-location: Huelva
Keywords: fluorescenc; photosynthesis; physiology; Quercus suber; water potential

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L; Aranda, I; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L.; Aranda, I.; Gil, L.; Pardos, J. A. (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential

Water stress responses of seedlings of four Mediterranean oak species - Fotelli, M N; Radoglou, K M; Constantinidou, H.-I. A (Tree Physiology, 2000)
Effects of water stress on phenology, growth, stomatal activity and water status were assessed from April to November 1996 in 2-year-old seedlings of Quercus frainetto Ten. (Quercus conferta Kit.), Quercus pubescens Willd., Quercus macrolepis Kotschy (Quercus aegilops auct.) and Quercus ilex L. growing in containers in northern Greece. All four species developed more than 50% of their total leaf area before the beginning of June—an adaptation to arid climates. Well-irrigated plants tended to develop greater individual leaf area, number of leaves per plant, total plant leaf area, height and root:shoot ratios than water-stressed plants, but the difference between treatments was not significant for any parameter in any species. Quercus macrolepis appeared to be the most drought-tolerant of the four species. It maintained the highest number of leaves of the smallest size and increased the proportion of fine roots during drought. In all species, drought caused significant decreases in stomatal conductance and predawn and midday water potentials from mid-July until the end of August, when the lowest soil water content and highest mean daily air temperatures and midday leaf temperatures occurred; however, the responses were species-specific. Among the four species, Quercus macrolepis sustained the highest stomatal conductance despite very low water potentials, thus overcoming drought by means of desiccation tolerance. Quercus ilex decreased stomatal conductance even before severe water stress occurred, thereby avoiding dessication during drought. Quercus pubescens had the highest water potential despite a high stomatal conductance, indicating that its leaf water status was independent of stomatal activity. Quercus frainetto was the least drought-resistant of the four species. During drought it developed very low water potentials despite markedly reduced stomatal aperture.
10.1093/treephys/20.16.1065
Keywords: Growth; Phenology; Quercus; Stomatal conductance; water potential

Plant functional types and ecosystem function in Mediterranean shrubland - Barradas, Díaz; Zunzunegui, M. (Journal of Vegetation Science, 1999)
This study attempts to identify Plant Functional Types (PFTs) within the scrub vegetation of the stabilized sand dunes of the Doñana National Park (southwestern Spain) and to explore possible links with ecosystem function. Two 10-km long transects were sampled along a gradient of water table depth from elevated and dry dunes to a border area close to the salt marsh. A matrix of cover values for 20 woody species × 58 plots and a matrix of 24 morphological and physiological traits × 20 species were analysed by means of DCA and TWINSPAN to identify the main vegetation types and PFTs. In order to know the predominant plant traits, the matrix of 20 species × 58 plots was multiplied by the 24 traits × 20 species matrix. The resulting 24 traits × 58 plots matrix was analysed by means of DCA. The main vegetation types coincide with the previous descriptions of the Park with Juniperus phoenicea woodland and xerophytic species dominating the top of the dunes and hygrophytic species with isolated Quercus suber trees in the depressions. Previous classifications of Mediterranean woody plants resulted in two main PFTs. The present analysis confirmed these two groups: maquis versus garrigue, but added four new groups. The analysis of the traits × plots matrix revealed that the main trend of variation is related to the water table gradient, while the traits related to the species of mature plant communities had little weight in the analysis because these communities are restricted to isolated patches.
Keywords: Doñana; Plant trait; Regeneration; water potential; Water table depth

Plant functional types and ecosystem function in Mediterranean shrubland - Barradas, Díaz; Zunzunegui, M (Journal of Vegetation Science, 1999)
This study attempts to identify Plant Functional Types (PFTs) within the scrub vegetation of the stabilized sand dunes of the Doñana National Park (southwestern Spain) and to explore possible links with ecosystem function. Two 10-km long transects were sampled along a gradient of water table depth from elevated and dry dunes to a border area close to the salt marsh. A matrix of cover values for 20 woody species × 58 plots and a matrix of 24 morphological and physiological traits × 20 species were analysed by means of DCA and TWINSPAN to identify the main vegetation types and PFTs. In order to know the predominant plant traits, the matrix of 20 species × 58 plots was multiplied by the 24 traits × 20 species matrix. The resulting 24 traits × 58 plots matrix was analysed by means of DCA. The main vegetation types coincide with the previous descriptions of the Park with Juniperus phoenicea woodland and xerophytic species dominating the top of the dunes and hygrophytic species with isolated Quercus suber trees in the depressions. Previous classifications of Mediterranean woody plants resulted in two main PFTs. The present analysis confirmed these two groups: maquis versus garrigue, but added four new groups. The analysis of the traits × plots matrix revealed that the main trend of variation is related to the water table gradient, while the traits related to the species of mature plant communities had little weight in the analysis because these communities are restricted to isolated patches.
Keywords: Doñana; Plant trait; Regeneration; water potential; Water table depth

Seasonal water potential changes and proline accumulation in Mediterranean shrubland species - Lansac, A R; ZABALLOS, J P; Martin, A (Plant Ecology, 1994)
We studied the water relations of 6 shrub and 3 tree species typical of the mediterranean climate region of central Spain to identify differential responses to water stress between and within species, and to determine if free proline concentration in leaves could be used as a water stress indicator. Predawn and midday water potentials (ffdw) on a seasonal basis, relative water content (RWC), leaf mass per area, foliar nitrogen and free proline concentrations were measured. The lowest water potentials were observed at the end of the summer, with recovery to higher water potentials in the fall and winter seasons. Species differed regarding the annual qdw fluctuation. Thymus zygis, Halimium viscosum, Genista hirsuta and Juniperus oxycedrus exhibited the most negative midday and predawn ~ w (both less than -6 MPa) with a large magnitude of response to changing conditions in soil moisture of the upper horizon of the soil. Lavandula pedunculata and Cistus ladanifer showed a moderate response. Quercus rotundifolia, Quercus faginea and Retama sphaerocarpa showed a modest response. The ~ w of different size individuals of Quercus rotundifolia and Cistus ladanifer were compared. The annual fflw fluctuation was greater in small individuals as compared to large individuals. In every species, there was an increase in proline concentration of bulk leaf tissues when predawn kVw dropped below -5 MPa. Small plants of Cistus ladanifer reached lower water potentials and also higher concentration of proline than bigger plants. Proline could possibly be used as a drought stress indicator in every species except Q. rotundifolia. It is suggested that in addition to water stress avoidance due to deep root systems, some mechanisms of water stress tolerance may operate among shrub and tree species of central Spain.
Keywords: Cistus ladanifer; Genista hirsuta; Halimium viscosum; Juniperus oxycedrus; Lavandula pedunculata; Leaf mass per area; nitrogen; Proline; Quercus faginea; Quercus rotundifolia; Relative water content; retama sphaerocarpa; Thymus zygis; water potential

Site-specific water relations and stomatal response of Quercus ilex in a Mediterranean watershed - Sala, Anna; Tenhunen, John D (Tree Physiology, 1994)
Intraspecific variations in the water relations and stomatal response of Quercus ilex L. were analyzed under field conditions by comparing trees at two locations within a Mediterranean watershed (l'Avic, Catalonia, NE Spain). Distinct environmental gradients exist between the two sites (referred to as ridge top at 975 m and valley bottom at 700 m) with greater soil depth for water storage, reduced radiation, reduced wind and higher water vapor pressure deficits at the valley bottom than at the ridge top. Osmotic adjustment and changes in tissue elasticiity did not significantly increase drought resistance in the trees studied. The leaf-to-air vapor pressure difference (Δw) threshold for inducing stomatal closure was higher at the ridge top (15.6 kPa MPa−1 ± 0.5 SE) than at the valley bottom (9.8 kPa MPa−1 ± 1.0 SE). However, increases in Δw beyond the threshold were followed by greater reductions in leaf conductance of trees at the ridge top than at the valley bottom. At both sites, maximum leaf conductance was related to predawn shoot water potential which, in turn, was related to watershed stream flow. The effects of water deficits during the dry summer of 1989 were more severe in trees at the valley bottom than at the ridge top. During periods of high evaporative demand, site-specific differences in the control of water loss led to more conservative water use by trees at the ridge top and, thus, to even greater drought avoidance (higher predawn water potentials) in late summer.
10.1093/treephys/14.6.601
Keywords: Mediterranean sclerophylls; oak forest; oak watershed; Osmotic potential; Stomatal conductance; water potential

Water as a determinant of the distribution of trees at the boundary of the Mediterranean zone. - Pigott, C D; Pigott, S (Journal of Ecology, 1993)
Investigates the water relations of two species, Quercus ilex and Tilia cordata (T. cordata) in southern France. Effect of drought on the growth in height and stem diameter of T. cordata; Importance of water supply in controlling both the small and large scale pattern of distribution of T. cordata.
Keywords: Quercus ilex; Tilia cordata; water potential

Évolution du potentiel hydrique foliaire et de la conductance stomatique de quatre chênes méditerranéens lors d'une période de dessèchement - Acherar, M; Rambal, S; Lepart, J (Ann. For. Sci., 1991)
Influence of soil drying on leaf water potential and stomatal conductance in four Mediterranean oak species. The water relations and the responses of 2 evergreen Quercus species (Quercus ilex L and Q suber L) and 2 deciduous species (Q afares Pomel and Q faginea Willd) were studied under experimental conditions. Two-yr old seedlings grown in 30-1 pots were subjected to a drying period where stomatal conductance, pre-dawn leaf water potential and minimum leaf water potential were measured. The results show that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al (1978, 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance (gsr max) as described by the reciprocal function gsr max = (-0.47 + 2.61 ψb)-1 for the evergreen oaks and gsr max = (-1.94 + 7.39 ψb)-1 for the deciduous ones. The differences between the 2 groups may partially explain their geographic distributions, and also lead to general questions concerning the mechanisms of water use in the Mediterranean oak species.
Keywords: deciduous; evergreen; mediterranean species; Quercus; Stomatal conductance; water potential; water stress

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E.; Bousquet, F.; Ducrey, M. (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E; Bousquet, F; Ducrey, M (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations